State, trust, and corporation - Maitland, Frederic William, 1850-1906 (Cambridge University Press, 2003)
Maitland's late, great essays on the historical origins of the state are collected in this volume. They contain a series of profound insights into the way the character of the state has been shaped by the non-political associations that exist alongside it - matters of continuing relevance today.
Keywords: Maitland, Frederic William, -- 1850-1906.; Maitland, Frederic William, -- 1850-1906; Law -- England.; Corporation law -- England.; State, The.; Droit -- Angleterre.; État.; Sociétés -- Droit -- Angleterre -- Législation.; LAW -- Jurisprudence.; LAW -- General Practice.; LAW -- Reference.; LAW -- Essays.; LAW -- Paralegals & Paralegalism.; LAW -- Practical Guides.; Corporation law; Law; State, The; England; Staat; Entstehung; Körperschaft; Recht; Fiducie.; Sociétés -- Droit.